Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1051/0004-6361/201322742
|View full text |Cite
|
Sign up to set email alerts
|

The evolving spectrum of the planetary nebula Hen 2-260

Abstract: Aims. We analysed the planetary nebula Hen 2-260 using optical spectroscopy and photometry. We compared our observations with the data from literature to search for evolutionary changes. We also searched for photomertic variability of the central star. Methods. The object Hen 2-260 was observed with the SAAO 1.0 m telescope (photometry) and the SALT telescope (low resolution spectroscopy). We also used archival high resolution Very Large Telescope spectra and Hubble Space Telescope imaging. The nebular line fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…6). The suggestion that they are rather peculiar and rare objects that may originate in binary systems (see Gorny et al 2010, for more details) has not been confirmed by photometric observations (Hajduk et al 2014;Hajduk, priv. comm.…”
Section: Spitzer Dust Subtypes Vs Agb Nucleosynthesis Predictionsmentioning
confidence: 99%
“…6). The suggestion that they are rather peculiar and rare objects that may originate in binary systems (see Gorny et al 2010, for more details) has not been confirmed by photometric observations (Hajduk et al 2014;Hajduk, priv. comm.…”
Section: Spitzer Dust Subtypes Vs Agb Nucleosynthesis Predictionsmentioning
confidence: 99%
“…The line ratios are reproduced rather well by pyCloudy using a black-body T eff = 26 000 K. Hajduk et al (2014) used a stellar atmosphere model which requires a higher temperature for the same number of ionizing photons: they find 35 000 K. Hajduk et al (2014) method (from the heating rate of the central star): their age (980 yr) approximately agrees with that estimated below from the kinematics. The 1D model of Gesicki et al (2014) predicted a parabolic shape for the velocity field, with an average expansion velocity somewhat smaller than the 3D estimation presented here.…”
Section: Hen 2-260 (Pn G0082+068)mentioning
confidence: 64%
“…The nebula is radiation bounded, except for a narrow cone along the symmetry axis where it is matter bounded. This object was discussed in Hajduk et al (2014), where it was analysed with spherically symmetric 1D Cloudy and Torun codes. They derived a distance to this PN of 12 kpc.…”
Section: Hen 2-260 (Pn G0082+068)mentioning
confidence: 99%
See 2 more Smart Citations